Combination of radiotherapy and immunotherapy for brain metastases: A systematic review and meta-analysis. (December 2019) - Petrelli, Fausto; De Stefani, Agostina; Trevisan, Francesca; Parati, Chiara; Inno, Alessandro; Merelli, Barbara; Ghidini, Michele; Bruschieri, Lorenza; Vitali, Elisabetta; Cabiddu, Mary; Borgonovo, Karen; Ghilardi, Mara; et al.
Highlights: There is a rationale for the combination of radiotherapy + immunotherapy (RT + IT). We have assessed the efficacy of RT + IT for brain metastases of solid tumors. Median pooled OS was 15.9 months in n = 30 studies with data available. One- and 2-year OS rates were 55 and 35% respectively. Addition of IT to RT lead to an improved OS (HR = 0.54, 95%CI 0.44–0.67; P < 0.001). Abstract: Radiotherapy (RT) represents a mainstay in the treatment of brain metastases (BMs) from solid tumors. Immunotherapy (IT) has improved survival of metastatic cancer patients across many tumor types. The combination of RT and IT for the treatment of BMs has a strong rationale, but data on efficacy and safety of this combination is still limited. A systematic search of PubMed, the Cochrane Central Register of Controlled Trials, and EMBASE was conducted. 33 studies were included for a total of 1520 patients, most of them with melanoma (87%). Median pooled OS was 15.9 months (95%CI 13.9–18.1). One- and 2-year OS rates were 55.2% (95% CI 49.3–60.9) and 35.7% (95% CI 30.4–41.3), respectively. Addition of IT to RT was associated with improved OS (HR = 0.54, 95%CI 0.44-0.67; P < 0.001). For patients with BMs from solid tumors, addition of concurrent IT to brain RT is able to increase survival and provide long term control.